The role of entrepreneurship education in shaping self-employment intentions: a TPB-based study of Malaysian TVET students - Isma Addi Jumbri; Eleeza F. Natasya Khairul Herman; Fauzan Fauzan; Mulyani Karmagatri; Sandy Setiawan; Dian Kurnianingrum (Institute of Advanced Engineering and Science, 2026)
Entrepreneurship education prepares technical and vocational education and training (TVET) students with the competencies and entrepreneurial mindset required for future business endeavors. Guided by the theory of planned behavior (TPB), this study examines how such education shapes students’ self-employment intentions (SEI). A quantitative survey was administered to 300 undergraduates at Universiti Teknikal Malaysia Melaka (UTeM), and the data were analyzed using correlation and regression methods. The results show that entrepreneurial intention is positively linked to attitude toward behavior (r=0.474), entrepreneurship education (r=0.416), subjective norms (r=0.374), and perceived behavioral control (r=0.346), with attitude identified as the most influential predictor, accounting for 22.4% of the variance. These outcomes emphasize the centrality of individual motivation and the enabling role of entrepreneurship education in cultivating entrepreneurial aspirations. The study highlights the strategic importance of embedding stronger entrepreneurship curricula in TVET institutions to enhance self-employment readiness and support national goals for workforce development and economic resilience. The findings resonate with Malaysia’s National Entrepreneurship Policy 2030 and the TVET empowerment agenda, pointing to the value of initiatives such as campus incubators, seed funding, and mentorship in transforming entrepreneurial intention into tangible venture creation.